Pengaruh frekuensi pemeriksaan pajak dan kualitas pemeriksa pajak terhadap tingkat kepatuhan wajib pajak badan - HUMALA SETIA (Jurnal Bisnis dan Akuntansi, 2015)
This Study was intended to obtain empirical proofs that tax audit frequency and quality of tax auditor have influence tax compliance level of companies. Procedure of data collecting done at this research is by propagating questioners to taxpayer trough survey mail as well as propagated in service point (TPT) at each tax service office to be delivered to taxpayer to or is reporting. Each letter to be addressed to company owner or manager. This is need to be done to be able to control the effect of understanding quality of taxation responsibility of tax payer. Beside, researcher make contact trough telephone to reconfrim and remind to the questioner which had been sent previous two week. While the adjustment of taking minimal sample according to the number of effective company taxpayer at regional office of directorate general of taxation of east part of Java I in each tax service office totally 200 taxpayer. Result of research using analysis of Strutural Equation Modelling (SEM) that frequency of tax audit have negative and significant influence to compliance level of company taxpayer. While, quality of tax auditor have positive and significant influence to compliance level of company taxpayer. Result of finding in this study also give more understanding of some factor in tax auditing activity having negative influence to compliance level of company taxpayer and try to optimize auditor quality in order to minimize detection error according to principle of equal treatment can be accomplished and eventually tax evasion activity could be lessened.